Children and adolescent beggars in Perú - Pazos Maldonado, Luis Enrique (2014)
This article aims at first at presenting sorne of the concepts on begging that have already been developed by scholars and jurists, considering legal, social, andpsychological perspectives. Subsequently, the author provides a synopsis of reality and the current situation of how our country addresses and faces this sad realíty; passing rules and following supranational provisions, developing programs that unfortunately fail to reduce or eliminate this harmful activity that thwarts the development of our children and adolescents.  Then the author refers to the notion of infancy and child development over time and within their community, and how they have achieved, in a short period of time, many rights in their favor. Finally, the author describes, what in his view, are sorne imperfections ofboth the law and its regulations; then he quotes sorne of the most important provisions in force for our country while including two flowcharts, one on MIMP coordination with other agencies and the second one describing the specif procedure set out under S.D. 001- 2005-MIMD ES.